Closed-loop oxygen control for patients with hypoxaemia during hospitalisation: a living systematic review and meta-analysis protocol - Alexia Gabriela da Silva Vieira; Caroline Gomes Mol; Bianca Maria Schneider Pereira Garcia; Emanuel dos Santos Pereira; Raquel Afonso Caserta Eid; Ana Carolina Pereira Nunes Pinto; Ricardo Kenji Nawa (BMJ Open)
Introduction Oxygen is the most common drug used in critical care patients to correct episodes of hypoxaemia. The adoption of new technologies in clinical practice, such as closed-loop systems for an automatic oxygen titration, may improve outcomes and reduce the healthcare professionals’ workload at the bedside; however, certainty of the evidence regarding the safety and benefits still remains low. We aim to evaluate the effectiveness, efficacy and safety of the closed-loop oxygen control for patients with hypoxaemia during the hospitalisation period by conducting a systematic review and meta-analysis.Methods and analysis MEDLINE, CENTRAL, EMBASE, LILACS, CINAHL and LOVE evidence databases will be searched. Randomised controlled trials and cross-over studies investigating the PICO (Population, Intervention, Comparator and Outcome) framework will be included. The primary outcomes will be the time in the peripheral oxygen saturation target. Secondary outcomes will include time for oxygen weaning time; length of stay; costs; adverse events; mortality; healthcare professionals’ workload, and percentage of time with hypoxia and hyperoxia. Two reviewers will independently screen and extract data and perform quality assessment of included studies. The Cochrane risk of bias tool will be used to assess risk of bias. The RevMan V.5.4 software will be used for statistical analysis. Heterogeneity will be analysed using I2 statistics. Mean difference or standardised mean difference with 95% CI and p value will be used to calculate treatment effect for outcome variables.Ethics and dissemination Ethical approval is not required because this systematic review and meta-analysis is based on previously published data. Final results will be published in peer-reviewed journals and presented at relevant conferences and events.PROSPERO registration number CRD42022306033.